Digital Economy Strategy In Labor Market And Its Impact On The Competitiveness Of Start-ups In Palestine – Prospects And Challenges - Kaci Yasmina (جامعة الوادي University of Eloued, 2024)
The digital economy has recently emerged as a focal point of scholarly and governmental attention, recognized for its potential to drive significant advancements in economic, financial, and technological spheres. This study delves into the influence of digital economic strategies on nascent enterprises, with a particular focus on the Palestinian context. Our analysis reveals that the systemic digitization of economic frameworks and strategic focus on digital initiatives have profoundly influenced the operations of these enterprises, notably in the realms of electronic banking and investment.This exploration offers insightful revelations into the realities and challenges encountered by emerging businesses within the digital economy in Palestine, highlighting their pivotal role in contemporary economic discourse.
Keywords: : Digital Economy Strategy; Startups; Palestinian Community.